A Kinetic View of Membrane Traffic Pathways Can Transcend the Classical View of Golgi Compartments - Pantazopoulou, Areti; Glick, Benjamin S. (Frontiers in Cell and Developmental Biology, 2019)
A long-standing concept is that the Golgi apparatus is composed of distinct compartments, but the molecular identities of those compartments have not been clearly described. The idea of a compartmentalized Golgi is challenged by the cisternal maturation model, which postulates that cisternae form de novo and then undergo progressive biochemical changes. Cisternal maturation could potentially be reconciled with Golgi compartmentation by defining compartments as discrete stages in the maturation pathway. These stages would be distinguished by the traffic pathways that are operating. A limitation of this approach is that multiple traffic pathways drive Golgi maturation, and their periods of operation can overlap, so a large number of stages would need to be defined. After attempting such an exercise based on the available data, we conclude that the concept of Golgi compartmentation has outlived its usefulness. Instead, we propose that the focus should be on the series of transitions experienced by a Golgi cisterna as different traffic pathways are switched on and off. These traffic pathways drive changes in resident protein composition. Transitions in traffic pathways are the fundamental, conserved determinants of Golgi organization. According to this view, the initial goal is to identify the relevant traffic pathways and place them on the kinetic map of Golgi maturation, and the ultimate goal is to elucidate the logic circuit that switches individual traffic pathways on and off as a cisterna matures.